Characterisation of bovine leukocyte Ig-like receptors. - Louise Hogan; Sabin Bhuju; Des C Jones; Ken Laing; John Trowsdale; Philip Butcher; Mahavir Singh; Martin Vordermeier; Rachel L Allen (PLoS ONE)
Leukocyte Immunoglobulin-like receptors (LILR) are innate immune receptors involved in regulating both innate and adaptive immune functions. LILR show more interspecies conservation than the closely related Killer Ig-like receptors, and homologues have been identified in rodents, primates, seals and chickens. The murine equivalents, paired Ig-like receptors (PIR), contain two additional immunoglobulin domains, but show strong sequence and functional similarities to human LILR. The bovine genome was recently sequenced, with preliminary annotations indicating that LILR were present in this species. We therefore sought to identify and characterize novel LILR within the Bos taurus genome, compare these phylogenetically with LILR from other species and determine whether they were expressed in vivo. Twenty six potential bovine LILR were initially identified using BLAST and BLAT software. Phylogenetic analysis constructed using the neighbour-joining method, incorporating pairwise deletion and confidence limits estimated from 1000 replicates using bootstrapping, indicated that 16 of these represent novel bovine LILR. Protein structures defined using protein BLAST predict that the bovine LILR family comprises seven putative inhibitory, four activating and five soluble receptors. Preliminary expression analysis was performed by mapping the predicted sequences with raw data from total transcript sequence generated using Genome Analyzer IIx (Illumina) to provide evidence that all 16 of these receptors are expressed in vivo. The bovine receptor family appears to contain receptors which resemble the six domain rodent PIR as well as the four domain LILR found in other species.